Dada and surrealism : a very short introduction - Hopkins, David . (Oxford University Press, 2004)
A stimulating introduction to the many debates surrounding the Dadaist and Surrealist movements, such as the Marquis de Sade's position as a Surrealist deity, attitudes towards the city, the impact of Freud, and attitudes towards women.